2012
DOI: 10.1111/j.1439-0426.2012.02024.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary phosphorus affected growth performance, body composition, antioxidant status and total P discharge of young hybrid sturgeon (♀Huso huso × ♂Acipenser schrenckii) in winter months

Abstract: Summary An 8‐week feeding trial was carried out using young hybrid sturgeon (♀Huso huso × ♂Acipenser schrenckii) to study the effects of dietary phosphorus (P) on growth performance, body composition, liver and serum antioxidant status as well as the effluent P content in the wintertime. Four puffed pellet diets were formulated to contain graded total P levels at 0.63, 1.15, 1.85, and 2.12%, respectively. Triplicate groups of hybrid sturgeon (494.21 ± 18.63 g) were reared in concrete ponds (2.0 × 1.2 × 1.4 m),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…Dietary P levels may affect antioxidant status of fish while that is poorly documented. For instance, hybrid sturgeon liver exhibited higher SOD, CAT and GSH‐Px activities when fed the lower dietary P (Jin, Wang, Tang, Xie & Dai ). In lower P groups (0.33% and 0.56%), no antioxidant responses were observed and this may not have been low enough to affect antioxidant responses of yellow catfish adversely (Zhu, Qiu, Ding, Duan & Wang ).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary P levels may affect antioxidant status of fish while that is poorly documented. For instance, hybrid sturgeon liver exhibited higher SOD, CAT and GSH‐Px activities when fed the lower dietary P (Jin, Wang, Tang, Xie & Dai ). In lower P groups (0.33% and 0.56%), no antioxidant responses were observed and this may not have been low enough to affect antioxidant responses of yellow catfish adversely (Zhu, Qiu, Ding, Duan & Wang ).…”
Section: Introductionmentioning
confidence: 99%
“…SOD activity affected by dietary P has been evaluated in many studies. Inhibited plasma SOD activity was also found in hybrid sturgeon ( ♀Huso huso × ♂Acipenser schrenckii ) and young taimen ( Hucho taimen ) after feeding low P diet (Jin et al, ; Wang et al, ). In the present study, fish in the low P groups (0 and 50 mg P/kg BW) showed inhibited ALP and SOD activity, indicating that fish were suffering oxidative stress because of the P deficiency.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, fish in the low P groups (0 and 50 mg P/kg BW) showed inhibited ALP and SOD activity, indicating that fish were suffering oxidative stress because of the P deficiency. Disturbance of P homeostasis in fish could induce significant physiological effects on fish including oxidative stress (Jin et al, ; Skonberg et al, ). Thus, fish would be susceptible to the outside environment such as pathogens or contaminants at the status of the disturbed homeostasis because of the inappropriate P addition in the diet (Chen et al, ; Sugiura et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations